Socio-demographic Characteristics of Hepato-cellular Carcinoma Patients attended at Tertiary Care Hospital in Dhaka City - Hossain, Md Akter; Huq, Md Saiful; Ahmad, Ashfaq (Journal of Current and Advance Medical Research, 2018)
Background: The hepatocellular carcinoma is one of the most common tumor. Objectives: The purpose of the present study was to see the socio-economic characteristics of hepatocellular carcinoma patients. Methodology: This cross sectional study was carried out in the Department of Radiology and Imaging in Dhaka Medical College, Dhaka and Banghabandhu Sheikh Mujib Medical University, Dhaka from January 2007 to May 2008 for a period of around one and half year. All the patients presented with hepatocellular carcinoma at the age group of more than 20 years with both sexes were selected as study population. The patients were undergone CT-scan examination and the confirmation was performed by histopathological examination. Result: A total number of 50 patients were recruited in this study after fulfilling the inclusion and exclusion criteria. Mean age of my study was 48.78 and SD ± 12.07. Out of 50 patients 43(86%) were male and 7(14%) female. Cultivator was 42% followed by service holder. Medical personnel were 2%. Illiterate group was the top of the list with 40% and most educated was 4%. Conclusion: In conclusion the hepatocellular carcinoma is most commonly occurred in middle age group with a predominance of male. Journal of Current and Advance Medical Research 2016;3(2):39-42